Penerapan Prinsip Akuntabilitas Dan Transparansi Dalam Pelayanan Publik Pada Kantor Camat Marisa - Hasman Umuri (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Principles of accountability and transparency essentially intended to assess the performance of a government, accountability and transparency is the basis for measuring thesuccess of the performance of the government, but many people’s perception that thegovernment considers that today many are not accountable, and aims to obtain transparan. Penelitian a description of the application of the principles of accountability andtransparency in public services at the district office districts marisa marisa pohuwato. Thisstudy uses qualitative research methods with the number of informants as many as tenpeople. Data were collected through interviews and document study. The results showed thatpublic participation is still low with an indication of the willingness of society and arroganceare still high for participating, the competence of the district office personnel are lacking inthe task that is given in result of a lack of training on basic tasks and functions of eachapparatus. It is suggested to all parties involved, especially the community to begin to changethe paradigm that does not understand the fundamental importance of the activities held bylocal authorities, and then to the associated apparatus are suggested to the leadership inorder to program the training activities regarding the duties and functions of each field.